Discovery of Novel Nav1.7-Selective Inhibitors with the 1H-Indole-3-Propionamide Scaffold for Effective Pain Relief - Gaoang Wang; Hang Wu; Yingying Wang; Xiangying Liu; Shuijiao Peng; Wenxing Wang; Meijing Wu; Yifei Liu; Ercheng Wang; Zhe Wang; Lei Xu; Xiaojian Wang; et al. (Research)
Nav1.7 is considered a promising target for developing next-generation analgesic drugs, given its critical role in human pain pathologies. Although most reported inhibitors with strong in vitro activity and high selectivity share the aryl sulfonamide scaffold, they failed to demonstrate marked clinical efficacy. Therefore, exploring new Nav1.7-selective antagonists is quite urgent to the development of next-generation analgesic drugs. Here, we report a highly effective 1H-indole-3-propionamide inhibitor, WN2, identified through an integrated drug discovery strategy. Notably, the structure of WN2 is quite different from previously reported aryl sulfonamide inhibitors. Molecular dynamics simulations and experimental findings reveal that the R configuration of WN2 (WN2-R) is the preferred form (IC50 = 24.7 ± 9.4 nM) within the VSDIV pocket of Nav1.7. WN2-R exhibits impressive analgesic effects in acute and chronic inflammatory pain, as well as neuropathic pain models in mice. Additionally, it displays favorable subtype selectivity and positive drug safety in acute toxicity studies. Pharmacokinetic studies indicate that WN2-R has high bioavailability (F = 20.29%), highlighting its considerable potential for drug development. Our study establishes WN2-R as a novel Nav1.7-selective inhibitor with a unique structural scaffold, offering a promising candidate for the next generation of analgesic drugs.